Upaya Penanggulangan Penyebaran Konten Pornografi di Media Sosial - Nurfitrah Pakaya; Mohamad Rusdiyanto U Puluhulawa; Julisa Aprilia Kaluku (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to determine efforts to overcome the spread of pornographic content on social media. This research is empirical research because it places primary data in the community as the main data that will be analyzed qualitatively. The research results show that efforts to overcome the spread of pornographic content on social media are carried out by providing guidance and counseling regarding the dangers and sanctions for spreading pornography in society, especially for students; Conduct dialogue both directly and via radio and other mass media. Apart from that, dialogue is also carried out with the wider community through community-based field activities, such as programs held for the community by the police, for example when the police are asked to provide a welcome and guidance to the community when there is an agenda in the sub-district and village; Carry out raid operations and process legally, namely the police, especially the Bone Bolango Police, carry out raids and operations at entertainment venues, hotels and accommodation, especially in boarding houses which may be used as immoral places. If found, the police will summon immoral perpetrators, including those who make pornographic videos and take legal action; and Providing protection for victims, by first receiving complaint reports, then collaborating with related parties to fulfill the victims' rights.